2011
DOI: 10.2169/internalmedicine.50.6179
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Kyphosis and Barrett's Esophagus in Japanese Patients

Abstract: Background Kyphosis is a risk factor for the presence of hiatal hernia, which is a strong predictor of Barrett's esophagus. However, the association between kyphosis and Barrett's esophagus has not yet been clarified. To investigate this relationship, the Cobb angle, a marker of kyphosis, was measured in patients with and without Barrett's esophagus. Methods From January 2006 to December 2010, 26 patients with long-segment Barrett's esophagus (LSBE) were retrospectively enrolled. As the comparative groups, 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…Thirteen studies were excluded, as they did not provide sufficient data (reasons for exclusion detailed in Appendix ). Data were extracted from 83 studies; however, 11 of these studies had to be excluded from the statistical analysis as they contained data from same populations already described in other articles . Our final statistical analysis included 72 studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen studies were excluded, as they did not provide sufficient data (reasons for exclusion detailed in Appendix ). Data were extracted from 83 studies; however, 11 of these studies had to be excluded from the statistical analysis as they contained data from same populations already described in other articles . Our final statistical analysis included 72 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Prevalence of HPI for different segment lengths of BE was detailed in 7 studies and data were suitable for meta‐analysis . Two articles had detailed data on ultrashort segment BE (USSBE, <1 cm) and they were not included in the short segment BE (SSBE) subgroup.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, smoking and alcohol consumption were not found to be associated with the development of BE in Western patients 76. A retrospective study in Japanese patients showed that kyphosis is a risk factor for the presence of long-segment BE 77. Significant differences in the Cobb angle, a marker of kyphosis, were found between long-segment BE and control patients (with SS BE or without BE).…”
Section: Risk Factorsmentioning
confidence: 94%
“…heartburn and regurgitation) are associated with progressive and asymmetrical degeneration of spinal elements. In particular, an increased Cobb angle increases the risk not only of symptoms but also the development of GERD . An increase in Cobb angle as a result of an increase in the number of vertebral kyphotic deformities and sagittal imbalance and a decrease in back muscle strength leads to an increase in intra‐abdominal pressure .…”
Section: Incidence and Severity Of Gerd And Spinal Deformitymentioning
confidence: 99%